The Effects of Leaf Extracts of Four Tree Species on Amygdalus pedunculata Seedlings Growth - Wang, Xiuqing; Zhang, Ruiqi; Wang, Jinxin; Di, Long; Wang, Huaibiao; Sikdar, Ashim (Frontiers in Plant Science, 2021)
Vegetation reconstruction is an urgent problem in fragile environment like coal mine subsidence areas. Amygdalus pedunculata is an important eco-economic shrub species that promotes wind prevention, sand fixation as well as soil and water conservation. The natural regeneration of pure Amygdalus pedunculata forests is difficult to achieve because of its low seed germination rate and weak seedling growth. A stereo-complex ecosystem could potentially promote the germination and seedling growth of A. pedunculata and establish a steady mixed plantation consisting of trees and shrubs. Here, laboratory and pot experiments were conducted to assess the effect of four tree species on morphological and physiological indexes of A. pedunculata. The laboratory experiment showed that A. pedunculata seed germination and seedling growth from Yuyang County (YC-1) and Shenmu County (SC-6) were higher when plants were treated with the aqueous leaf extracts of Pinus sylvestris, Broussonetia papyrifera, and Pinus tabulaeformis compared with Populus simonii at concentrations of 2.5% (E2.5) and 5% (E5). Furthermore, the donor leaf extract was more sensitive to YC-1 than to SC-6. The pot experiment showed that the E2.5 and E5 treatments with the aqueous leaf extracts on the three tree species had strong promoting effects of seedling length, root length, seedling fresh weight, root fresh weight, and ground diameter for YC-1. The activity of catalase of A. pedunculata seedlings first increased and then decreased, while the activity of peroxidase, superoxide dismutase, roots, and the contents of soluble protein and chlorophyll decreased; the opposite patterns were observed for malondialdehyde, soluble sugar, cell membrane permeability, and proline were the opposite. Synthetical allelopathic effect index values of the leaf extracts of the three species on YC-1 were as follows: P. sylvestris>B. papyrifera>P. tabulaeformis (E2.5 to E20). Therefore, P. sylvestris and B. papyrifera could be used to promote the growth of A. pedunculata seedlings as well as for the construction of mixed plantations in coal mine degradation areas. Generally, this study provides new insight into the creation of stereo-complex ecosystems (P. sylvestris + A. pedunculata and B. papyrifera + A. pedunculata) in arid fragile environment.